Microbial Biofilms and Breast Tissue Expanders. (16th July 2013) - Karau, Melissa J.; Greenwood-Quaintance, Kerryl E.; Schmidt, Suzannah M.; Tran, Nho V.; Convery, Phyllis A.; Jacobson, Steven R.; Bite, Uldis; Clay, Ricky P.; Petty, Paul M.; Johnson, Craig H.; Mandrekar, Jayawant; Patel, Robin
Abstract : We previously developed and validated a vortexing-sonication technique for detection of biofilm bacteria on the surface of explanted prosthetic joints. Herein, we evaluated this technique for diagnosis of infected breast tissue expanders and used it to assess colonization of breast tissue expanders. From April 2008 to December 2011, we studied 328 breast tissue expanders at Mayo Clinic, Rochester, MN, USA. Of seven clinically infected breast tissue expanders, six (85.7%) had positive cultures, one of which grew Propionibacterium species. Fifty-two of 321 breast tissue expanders (16.2%, 95% CI, 12.3–20.7%) without clinical evidence of infection also had positive cultures, 45 growing Propionibacterium species and ten coagulase-negative staphylococci. While vortexing-sonication can detect clinically infected breast tissue expanders, 16 percent of breast tissue expanders appear to be asymptomatically colonized with normal skin flora, most commonly, Propionibacterium species.